Selecting the lag length for the MGLS unit root tests with structural change: A warning note for practitioners based on simulations - Ricardo Quineche; Gabriel Rodríguez (Econometrics, 2017)
This is a simulation-based warning note for practitioners who use the MGLS unit root tests in the context of structural change using different selection lag length criteria. With T=100 , we find severe oversize problems when using some criteria, while other criteria produce an undersizing behavior. In view of this dilemma, we do not recommend using these tests. While such behavior tends to disappear when T=250 , it is important to note that most empirical applications use smaller sample sizes such as T=100 or T=150 . The ADFGLS test does not present an oversizing or undersizing problem. The only disadvantage of the ADFGLS test arises in the presence of MA(1) negative correlation, in which case the MGLS tests are preferable, but in all other cases they are very undersized. When there is a break in the series, selecting the breakpoint using the Supremum method greatly improves the results relative to the Infimum method.
Keywords: C22; C52; 330; unit root tests; structural change; truncation lag; GLS detrending; information criteria; sequential general to specific t-sig method